(untitled) (Mustansiria Dental Journal, 2024)
Aims: This investigation aimed to examine the impact of autoclave sterilization on the cyclic fatigue of AF-F ONE, ProTaper Ultimate, and ProTaper Gold. Materials and Methods: Sixty #25 rotary files were categorized into groups as follows: AF-F ONE (Group A), ProTaper Ultimate (Group B), and ProTaper Gold (Group C). Additionally, within each group, there were subdivisions into sterilized and non-sterilized subgroups. Sterilized instruments underwent five cycles of sterilization by autoclave. Cyclic fatigue resistance was evaluated using a simulated canal featuring a single curvature (60° angle, 5-mm radius). Files were operated until fracture, and time and number of cycles to fracture (NCF) were recorded. Statistical analysis: One-way ANOVA, Post hoc Tukey test, and independent t-test. Results: ANOVA indicated a significant difference among non-sterilized groups (p < 0.05). Tukey’s test showing a notable difference between AF-F ONE and ProTaper Ultimate/ProTaper Gold (p < 0.05), but not between the latter two (p>0.05).AF-F ONE significantly decreased after autoclave sterilization (p < 0.05), while ProTaper Ultimate and ProTaper Gold remained unaffected (p>0.05). Conclusion: Autoclave sterilization significantly affected the cyclic fatigue of AF-F ONE, whereas ProTaper Ultimate and ProTaper Gold demonstrated resilience.